Meteorological Drought Analysis Based on Satellite Rainfall Data in the Slahung Sub Watershed - Friyana, Acha Octa; Harisuseno, Donny; Bisri, Mohammad (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
As a country in the tropics, Indonesia experiences drought almost yearly. However, prevention is still very slow, particularly in East Java Province, making it a prolonged problem. Meteorological drought is closely related to climate anomalies or weather instability that result in changes in rainfall patterns. Meteorological drought is analyzed using the EDI (Effective Drought Index) method. As a form of meteorological drought disaster mitigation, good and evenly distributed rainfall data is needed. Satellite technology such as CHIRPS can complement the uneven distribution of rain stations and areas difficult to reach by meteorological stations. The analysis shows that the worst drought occurred in 2005 with a minimum index value of -2.41, followed by 2007 (-1.94), 2012 (-1.55), 2017 (-1.62), and 2019 (-1.50). Based on the trend of drought events that occur every 2 to 5 years. This study’s results indicate that satellite rainfall data can help provide a more complete picture of drought conditions in the Slahung Sub watershed. With this study, an early warning system for drought mitigation is expected to be developed, and more effective measures can be planned to deal with future drought disasters in Ponorogo Regency.